O espaço no berçário - Silva, Géssica Valéria Martins da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present work aims to show how the non - domiciliary collective spaces and the importance of their organization should be focused on the physical space of the day care center. In order to show the environments that are fundamental, in other words, that all daycare centers should have, the theme was chosen based on the experiences of the Supervised Internship of Teaching in Early Childhood Education - Nursery, carried out by two students of the Pedagogy Licentiate course of the Faculty of Sciences and Technology Unesp campus of Presidente Prudente. One of the experiences occurred in a private institution and the other in a public institution. The private institution presents fundamental environments for the comfort and learning of children, such as rest room, activity room, nursery and lactario, which the public day care does not present, it is important to point out that the public institution is an old building, so doesn't dispose of these spaces, it was adapted as possible. During the observation of the spaces of the institutions and analyzing some documents we understand the importance of the physical space, transforming into a welcoming environment, which guarantees comfort, physical security, offers opportunities and challenges for the construction of the identity and autonomy of the child, allowing them to express themselves in their diverse languages, with a learning that respect them as social subjects, respecting the right to be a child. The materials and furniture that were far from the children today should be within their reach. The organization of this environment may change as planned...

O presente trabalho tem como objetivo mostrar como devem ser os espaços não domiciliares coletivos e a importância da sua organização com foco no espaço físico da creche. Buscar mostrar os ambientes que são fundamentais, ou seja, que todas as creches deveriam ter, o tema foi escolhido a partir das vivências realizadas no Estágio Supervisionado de Prática de Ensino na Educação Infantil - Creche, realizado por duas alunas do curso de Licenciatura de Pedagogia da Faculdade de Ciências e Tecnologia Unesp campus de Presidente Prudente. Uma experiência ocorreu em uma instituição privada e a outra em uma instituição pública. A instituição privada apresenta ambientes fundamentais para o conforto e aprendizagem das crianças, como sala de descanso, sala de atividades, sala de amamentação e lactário, que a creche pública não apresenta, é importante salientar que a instituição publica é antiga, por isso não dispões desses espaços, foi apenas se adaptando como podia. Durante a observação dos espaços das instituições e analisando alguns documentos. Compreendemos a importância que têm o espaço físico, se transformando em ambiente de acolhimento, que garanta conforto, segurança física, ofereça oportunidades e desafios para a construção da identidade e autonomia da criança, permitindo se expressarem em suas diversas linguagens, com uma postura que as respeitem como sujeitos sociais de direitos, respeitando o direito de ser criança. Os materiais e mobiliários que ficavam longe das crianças hoje devem ficar ao seu alcance...
Keywords: Educação - Estudo e ensino; Lactente; Espaço (Arquitetura); Berçarios; Education - Study and teaching